[Image 17] - Smith, Captain Sir William [?ob. 1732] (My University, 1804)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View from Fannat Point signal station looking towards Dunree Fort or Battery and Fahan drawn by Sir Wm Smith in 1804.
Keywords: Fannat Point; Dunree; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810